The Role of Vitamin D Deficiency in Allergic Rhinitis in Children - I Gusti Ayu Prema Yani Sidemen; Ida Ayu Mirah Agung; Shelly Kartika Wardani; Ade Manik Dharma S (CV Edujavare Publishing, 2026)
Vitamin D deficiency remains a global health concern, including in tropical countries such as Indonesia, where many children still experience inadequate levels. Beyond its role in bone health, vitamin D is essential in immune regulation. Allergic rhinitis, a common condition in children, involves inflammation of the nasal mucosa and can negatively impact quality of life, learning, and daily activities. This study aims to review current evidence on the relationship between vitamin D deficiency and the incidence and severity of allergic rhinitis in children.This research used a narrative review approach by systematically searching PubMed and Google Scholar for relevant articles published between 2014 and 2024. The inclusion criteria focused on original studies involving children under 18 years that examined vitamin D levels or supplementation in relation to allergic rhinitis.Findings indicate that vitamin D plays an immunomodulatory role by reducing IgE levels, regulating cytokines, and enhancing T-regulatory cells. Several studies show that low vitamin D levels are associated with increased risk, severity, and poorer treatment outcomes of allergic rhinitis. However, some studies report inconsistent results.In conclusion, vitamin D deficiency may contribute to allergic rhinitis in children, although further research is needed to confirm this relationship.